Food Hypersensitivity in Children Aged 0–3 Years of the Lviv Region in Ukraine: A Cross-Sectional Study - Matsyura, Oksana; Besh, Lesya; Borysiuk, Olena; Gutor, Taras; Malska, Andriana; Kovalska, Oksana; Besh, Olesia; Sorokopud, Olena; Vari, Sandor G. (Frontiers in Pediatrics, 2022)
Aim: To determine the prevalence and to estimate factors associated with food hypersensitivity in young children of the Lviv region in Ukraine. Methods: A prospective cross-sectional survey study was conducted between 2016 and 2017 in the Lviv region of Ukraine. A specially designed questionnaire about food hypersensitivity of young children developed and validated by M. J. Flokstra-de Blok was used after translation into the Ukrainian language. The questionnaire included 34 questions, grouped into general and detailed information. Parents of children aged 0–3 years were asked to complete the questionnaire at pre-schools and medical institutions. Results: Among 4,500 distributed questionnaires, 3,214 (71%) were completed and processed. Parents reported that 25% of their young children had food hypersensitivity. According to the survey the most common agents involved in food hypersensitivity in young children were cow's milk (34%), egg (28%), and wheat (24%). Hypersensitivity to milk occurred in 50% of children in the age group of 1–2 years. Regional differences associated with food hypersensitivity were also found. Namely, in the Carpathians, there was more hypersensitivity to fish (27%) and honey (22%) than in other regions, while hypersensitivity to soy was detected mostly in Lviv City residents (8.5%). Unknown causes of food hypersensitivity were highly reported (34%) in the Carpathians. Conclusion: Prevalence and some distinctiveness of food hypersensitivity revealed in four geographic and climate zones as well as in Lviv City have a considerable practical use for formulation of recommendations for children with food hypersensitivity.